2012
DOI: 10.1111/j.1600-0897.2012.01104.x
|View full text |Cite
|
Sign up to set email alerts
|

Placental Villous Expression of TNFα and IL‐10 and Effect of Oxygen Tension in Euploid Early Pregnancy Failure

Abstract: Increased levels of TNFα and decreased levels of receptors in miscarriage villous tissue confirm an excessive placental inflammation in miscarriage patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 58 publications
0
17
1
1
Order By: Relevance
“…TNF-α has been shown to be increased in euploid compared to aneuploid miscarriages, as well as increased compared to the euploid pregnancies that survive [13,[72][73][74]79]. This increase has also been noted in their peripheral blood.…”
Section: Tnf-αmentioning
confidence: 68%
See 3 more Smart Citations
“…TNF-α has been shown to be increased in euploid compared to aneuploid miscarriages, as well as increased compared to the euploid pregnancies that survive [13,[72][73][74]79]. This increase has also been noted in their peripheral blood.…”
Section: Tnf-αmentioning
confidence: 68%
“…These cells also release IFN-γ to promote inflammation. It has been shown to be elevated in RPL patients [13,72,78,79,124]. Significant associations between RPL and the IFN-γ(+874) polymorphisms have been found [115,119,120].…”
Section: Ifn-γmentioning
confidence: 95%
See 2 more Smart Citations
“…However, it was shown that with the stopping of the embryo development the concentration and ratio of pro and antiinflammatory cytokines (particularly, TNFα and IL10) in the peripheral blood of women and in the chorionic villi depend on the embryo kary otype (Calleja Agius et al, 2012). The authors assume the existence of different mechanisms for the elimina tion of embryos with a normal and abnormal karyo type.…”
Section: Discussionmentioning
confidence: 99%